Comparative analysis of farmers' selection criteria for cowpea (Vigna unguiculata) varieties in Niger and Burkina Faso - Ishikawa, H.; Drabo, I.; Boukar, O.; Fatokun, C.; Muranaka, S. (2019)
A comparative analysis of farmers’ preferences on improved cowpea varieties was carried out based on the data obtained from farmers’ participatory varietal selection and questionnaire survey undertaken in south-eastern Niger and north-central Burkina Faso. The grain yield was consistently the most important and common selection criterion for farmers in both countries, with a significant influence of other traits, including balance between grain and fodder yields, earliness, seed characteristics, and resistance to Striga gesnerioides in their variety selection process. In other words, if the variety had enough yield, the farmers’ selection of the variety was separated from the second criterion reflecting farmers’ demand specific to their social and environmental conditions, such as tradition, marketing, assets, rainfall, and biotic and abiotic stresses in the region. Key criteria for farmers’ variety selection were obtained as well as an understanding of the potential of participatory activities to improve strategies in cowpea breeding and dissemination targeting these regions.